In vitro and in silico Analysis Alnustone Induced Anticancer Effects in Human Gastric Cancer - Xu, Na; Zhao, Yixiu (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: A growing number of people are at risk for gastrointestinal disorders due to dietary modifications and excessive consumption of processed food. Gastric Cancer (GC) ranks fifth in terms of frequency of diagnosis and is the third most common cause of cancer-related deaths worldwide. Objectives: The current work demonstrated the anti-cancer potential of Alnustone against stomach cancer in AGS cell lines. Materials and Methods: The cell viability study was performed to determine the IC50 value for the Alnustone. The effect of Alnustone on the activity of Caspase-3, -8 and -9 was estimated by utilizing commercially available colorimetric assay kits. Also, molecular docking analysis was performed for the Caspase-3, -8, -9, BAX, BCL-2, and p53 to identify the interactions with the Alnustone. Results: The results depicted that treating the AGS cell line with Alnustone significantly increased the level of caspases, indicating the anti-cancer property of Alnustone. The molecular docking analysis has revealed a promising finding: Alnustone demonstrated a better interaction with Caspase-3 (Binding Affinity (BA)=-6.2 kcal/ mol; RMSD=1.877Å) and Caspase-8 (BA=-6.1 kcal/mol; RMSD=1.092Å), surpassing its interaction with Caspase-9 (BA=-6.0 kcal/mol; RMSD=1.596Å) and BCL-2 (-6.6 kcal/mol; RMSD=2.5Å) based on the number of interacted hydrogen bonds. This suggests a potential strategy for the future: targeting Alnustone to enhance Caspase-3 activity, which could lead to a positive correlation with the expression of Caspase-8 (R=0.46; p-value=4e-24) and Caspase-9 (R=0.27; p-value=1.1e-08). However, Caspase-3 was negatively correlated with the expression of Bcl-2 (R=-0.014; p-value=0.77). Conclusion: The study results show that Alnustone is a strong contender for GC treatment since it induces apoptosis in AGS cells and exhibits a comparable correlation in in silico investigations.
Keywords: ADMET; Alnustone; Caspase; Gastric cancer; Molecular docking.